THE IMPORTANCE OF DAILY ROUTINE AND ENVIRONMENT IN THE GROWTH AND DEVELOPMENT OF CHILDREN AND ADOLESCENTS - Кулиев Сердар Батырович; Косимов Хайруддин Олимович (World Scientific Research Journal, 2025)
Abstract: The article examines the impact of daily routine and environmental factors on the growth and development of children and adolescents. The key principles of a healthy lifestyle, including balanced nutrition, physical activity, adequate sleep, and psychological comfort, are analyzed. Special attention is given to ecology and the surrounding environment as important aspects of shaping the health of the younger generation.